2021
DOI: 10.1111/jpn.13537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding high‐dosing Aspergillus oryzae phytase to corn–wheat–soybean meal‐based basal diet on growth performance, nutrient digestibility, faecal gas emission, carcass traits and meat quality in growing‐finishing pigs

Abstract: This study tests the effects of supplementation of high-dosing Aspergillus oryzae phytase into the corn-wheat-soybean meal (SBM)-based basal diet on growth performance, nutrient digestibility, faecal gas emission, carcass traits and meat quality in growing-finishing pigs (29.73-110.86 kg live weight; 70-day-old to 166-day-old).A total of 56 crossbred pigs [(Landrace × Yorkshire) × Duroc] were divided into two dietary groups for a 96-day experiment (growing period, days 0-42; finishing period, days 43-96) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…In addition, phytase reduces the necessary complement of minerals from non-renewable sources to diets, reducing nutritional costs as well as phosphorus emissions into the environment [ 7 , 12 , 13 ]. Some studies have also shown that phytase at higher doses (above 2500 FTU/kg) results in a more favorable growth performance in pigs than standard phytase doses (usually levels well over 500 FTU/kg and up to 2500 FTU/kg) [ 14 , 15 , 16 ]. On the other hand, it has been found that dietary supplementation with high doses of phytase can have some beneficial effects on carcass quality parameters such as back-fat thickness in growing–finishing pigs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, phytase reduces the necessary complement of minerals from non-renewable sources to diets, reducing nutritional costs as well as phosphorus emissions into the environment [ 7 , 12 , 13 ]. Some studies have also shown that phytase at higher doses (above 2500 FTU/kg) results in a more favorable growth performance in pigs than standard phytase doses (usually levels well over 500 FTU/kg and up to 2500 FTU/kg) [ 14 , 15 , 16 ]. On the other hand, it has been found that dietary supplementation with high doses of phytase can have some beneficial effects on carcass quality parameters such as back-fat thickness in growing–finishing pigs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also shown that phytase at higher doses (above 2500 FTU/kg) results in a more favorable growth performance in pigs than standard phytase doses (usually levels well over 500 FTU/kg and up to 2500 FTU/kg) [ 14 , 15 , 16 ]. On the other hand, it has been found that dietary supplementation with high doses of phytase can have some beneficial effects on carcass quality parameters such as back-fat thickness in growing–finishing pigs [ 16 ]. Cauble et al [ 17 ] and Gebert et al [ 18 ] reported that dietary phytase could moderate muscle fatty acid profiles in chickens and pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The use of microbial phytase in feed mixtures with legume seeds has been evaluated in only a few nutritional tests so far, but the current research focuses on examining the effectiveness of the use of phytase in fatteners under typical commercial production conditions [9]. Some studies have shown that phytase in higher doses results in more advantageous growth performances in pigs than when using standard phytase doses (usually levels well over 500 FTU/kg and up to 2500 FTU/kg) [13][14][15][16]. On the other hand, feed mixtures with higher enzyme doses can be more expensive.…”
Section: Introductionmentioning
confidence: 99%